2022
DOI: 10.18632/aging.204081
|View full text |Cite
|
Sign up to set email alerts
|

CCL19 has potential to be a potential prognostic biomarker and a modulator of tumor immune microenvironment (TIME) of breast cancer: a comprehensive analysis based on TCGA database

Abstract: The development of cancer was determined by not only the intrinsic properties of cancer cells, but also the communication between cancer cells and tumor microenvironment (TME). We applied ESTIMATE and CIBERSORT algorithms to calculate the immune/stromal component and tumor-infiltrating immune cells (TICs) in TME of BC. The results showed that immune component in TME predicted patients’ survival and associated with progression of BC. Differentially expressed genes (DEGs) were primarily enriched in immune-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Interestingly, we discovered that most immunomodulators were highly expressed in the low-risk group, which contradicted our finding that the high-risk group would respond better to immunotherapy. Several findings demonstrated that the high expression of CCL11 and CCL19 predicts better OS of BRCA 67,68 , and Li et al 69 indicated that the high expression of CCL21 is highly associated with a lower distant recurrence rate of BRCA, through increasing the infiltration of CD8+T cells, thus, we confirmed that these studies may explain the up-regulation of immunomodulators in the low-risk group. Consequently, we hypothesized that the high-risk group would respond better to immunotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, we discovered that most immunomodulators were highly expressed in the low-risk group, which contradicted our finding that the high-risk group would respond better to immunotherapy. Several findings demonstrated that the high expression of CCL11 and CCL19 predicts better OS of BRCA 67,68 , and Li et al 69 indicated that the high expression of CCL21 is highly associated with a lower distant recurrence rate of BRCA, through increasing the infiltration of CD8+T cells, thus, we confirmed that these studies may explain the up-regulation of immunomodulators in the low-risk group. Consequently, we hypothesized that the high-risk group would respond better to immunotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…CCL19 facilitates the secretion of IL-6 and IL-1β by DC cells, which promote tumor growth in triple-negative breast cancer (TNBC), leading to tumor invasion and worse prognosis in patients [31]. The latest research found CCL19 is a potential prognostic biomarker and is signi cantly correlated with TILs in breast cancer [32]. This study found that CCL19 was signi cantly elevated in tumor tissue in breast cancer and was signi cantly positively correlated with the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological characteristics included age, gender, grade and tumor node metastasis (TNM) stage. Survival and survminer packages in R were used for survival analysis, the same as our previous research ( 29 ). We used Kaplan–Meier plot and log-rank to test the correlations between molecular subtypes and overall survival (OS) of GC patients.…”
Section: Methodsmentioning
confidence: 99%